(untitled) (Contextos: Estudios de Humanidades y Ciencias Sociales, 2019)
Considering the female characters that were a constant in the narrative of Maria Luisa Bombal and, perhaps, little understood by the modesty of the time, they become strong today and with an unequivocal voice of the feeling that underlies their deeds: frustration, dissatisfaction and, finally, resignation before a cultural and moral reality that surpasses them. In this sense, his work La última Niebla (1934) will be briefly commented on those aspects in which the inhibited feelings of the woman emerge.